Evaluating the Role of Advanced Energy-Efficient Technologies in Promoting Sustainability in Nigeria’s Construction Industry - Unegbu, Hyginus Chidiebere Onyekachi; YAWAS, Danjuma (Jurnal Pengabdian KOLABORATIF, 2026)
This study evaluates the impact of advanced energy-efficient technologies on sustainability within the Nigerian construction sector, focusing on their effects on energy consumption, cost reduction, environmental benefits, and social impacts. A quantitative research approach was employed, using structured questionnaires administered to a total of 123 construction professionals across 150 infrastructure projects in Nigeria. The respondents included architects (n=30), civil and structural engineers (n=38), project managers (n=32), and other construction specialists such as quantity surveyors and support staff (n=23). The analysis included descriptive statistics, ANOVA, and multiple regression analysis to evaluate the relationships between technology adoption and sustainability outcomes. The results indicate strong consensus among respondents that energy-efficient technologies lead to reduced energy consumption (mean=4.2, SD=0.83) and long-term cost savings (mean=4.0, SD=0.92). Environmental benefits were rated highly (mean=4.3, SD=0.68), while social impacts were perceived as less significant (mean=3.7, SD=0.75). ANOVA results revealed statistically significant differences in perceptions based on professional roles (F(3,119)=5.24, p=0.002), with architects showing the strongest agreement regarding the effectiveness of these technologies. Multiple regression analysis identified perceived cost savings (β=0.34, p<0.001) and environmental impact (β=0.29, p<0.001) as the most influential predictors of technology adoption, followed by stakeholder awareness (β=0.22, p<0.001) and social benefits (β=0.15, p=0.003). The model accounted for 76% of the variance in adoption rates (R²=0.76), suggesting robust explanatory power. These findings highlight the critical role of advanced energy-efficient technologies in promoting sustainability in the Nigerian construction sector. They also emphasize the need for targeted educational programs and policy reforms to improve stakeholder awareness, especially of the social and community benefits, to drive broader and more inclusive adoption.